Compositional Changes during Papaya Fruit Ripening (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to investigate compositionalchanges during ripening of ‘Baladi’, ‘Ekostika I’ and ‘Ekostika II’papaya fruit cultivars at 20 ±1 ⁰C and 85% - 90% relative humidity. Thefruits of the three cultivars exhibited a typical climacteric pattern ofrespiration with peak of respiration of 82, 92 and 98 mg CO 2 / kg-hr,reached after 10 days in the three cultivars, respectively. Weight loss,total soluble solids (TSS), total sugars and ascorbic acid contentprogressively increased during ripening of the three papaya cultivars.More increase in TSS and total sugars was observed after the climactericpeak of respiration. Fruit tissue firmness and total phenolic compoundsdecreased continuously during ripening in the three cultivars. Reducingsugars, total protein and titratable acidity steadily increased to reach apeak, which coincided with the climacteric peak of respiration, andsubsequently decreased afterwards. The local ‘Baladi’ cultivar had alower respiration rate, more firm and less weight loss during ripening,which may indicate a longer shelf-life than the other two introducedcultivars. On the other hand, the introduced cultivars were higher inTSS, total and reducing sugars and ascorbic acid content and lower intitratable acidity and phenolic compounds, which may reflect a bettereating quality.
Keywords: Papaya fruit; compositional changes; fruit ripening